Carvedilol Analogue Inhibits Triggered Activities Evoked by Both Early and Delayed Afterdepolarizations - Maruyama, Mitsunori (2012)
BACKGROUND: Carvedilol and its analogues suppress delayed afterdepolarizations (DADs) and catecholaminergic polymorphic ventricular tachycardias by direct action on the cardiac ryanodine receptor (RyR2). OBJECTIVE: We tested a hypothesis that carvedilol analogue may also prevent triggered activities (TAs) through the suppression of early afterdepolarizations (EADs). METHODS: Intracellular Ca(2+) and membrane voltage were simultaneously recorded using optical mapping technique in Langendorff-perfused mouse and rabbit hearts to study the effect of carvedilol analogue, VK-II-36 that does not have significant beta-blocking effects. RESULTS: Spontaneous intracellular Ca(2+) elevations (SCaEs) during diastole was induced by rapid ventricular pacing and isoproterenol infusion in intact rabbit ventricles. Systolic and diastolic SCaEs were simultaneously noted in Langendorff-perfused RyR2 R4496(+/−) mouse hearts after creating atrioventricular block. VK-II-36 effectively suppressed SCaEs and eliminated TAs observed in both mouse and rabbit ventricles. We tested the effect of VK-II-36 on EADs using a rabbit model of acquired long QT syndrome in which phase-2 and phase-3 EADs were observed in association with systolic SCaEs. VK-II-36 abolished the systolic SCaEs and phase-2 EADs, and greatly decreased the dispersion of repolarization and the amplitude of phase-3 EADs. VK-II-36 completely prevented EAD-mediated TAs in all ventricles studied. CONCLUSION: A carvedilol analogue, VK-II-36 inhibits ventricular tachyarrhythmias in intact mouse and rabbit ventricles by suppression of SCaEs, independent of beta-blocking activity. The RyR2 may be a potential target for treating focal ventricular arrhythmias triggered by either EADs or DADs.